RHETORIC IN EXPOSITORY ESSAY OF THE FOURTH SEMESTER ENGLISH STUDENTS IN THE FACULTY OF CULTURAL STUDIES - NISA’, FAKHRUN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Rhetoric, Expository or analysis essay, Comparison and ContrastEssay, English Students of Faculty of Cultural Studies. There are different ways to deliver ideas inside the heads effectively. Here, rhetoric is the best way to learn how to deliver any thought or idea using good structure and organization in an effective way. Although rhetoric is much closed with speaking or persuasion, it can be applied in writing process especially for academic essays. Here, the researcher wants to knowThe data are the 30 expository essays written on 24 May 2014 by the fourth semester English students in the Faculty of Cultural Studies. There, this research is a textual analysis. In analyzing the data, the researcher does not include the whole essays from the students, because there are three essays do not have criteria as it was determined by the researcher. Then, the researcher analyzed it by using essay checklist proposed by Oshima and Hogue.From the finding, the researcher found two data which do not have thesis statement and twenty four data which have clearly focused on the thesis statement for the whole essay in the introductory paragraph. In the body paragraph were found twenty five data which have clearly topic sentence with the controlling idea, twenty two data which have sufficient supporting details, and twenty six data which have paragraph support only one main idea.Based on the findings, the researcher concludes that the most of the essay written by fourth semester English students in the faculty of Cultural Studies is have good essay organization. Then, it is suggested that the students think rhetorically in delivering their ideas in writing essays. Besides, the researcher also suggests the next researcher to analyze rhetoric and its influences by using other subjects.